Effects of increasing dietary wheat middlings on nursery pig growth performance - J A De Jong; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2011)
A total of 180 nursery pigs (PIC 327 × 1050, initially 25.2 lb BW) were used in a 21-d trial to evaluate the effects of increasing dietary wheat middlings on growth performance. Pens of pigs were balanced by initial BW and were randomly allotted to 1 of 5 dietary treatments with 6 replications per treatment. The 5 corn-soybean meal-based diets contained 0, 5, 10, 15 or 20% wheat middlings. Overall (d 0 to 21), pigs fed increasing wheat middlings had decreased ADG (linear, P<0 .05) and ADFI (linear, P<0 .005), but F/G was not affected by dietary wheat middlings. Despite the linear decrease in ADG and ADFI, the biggest reduction in performance was not observed until wheat middlings increased beyond 15% of the diet. This suggests that in some cases, the slight decrease in ADG with a low inclusion of wheat middlings (<15%) to the diet might be economically justified, so its inclusion needs to be evaluated on an income over feed costs basis.; Swine Day, Manhattan, KS, November 17, 2011
Keywords: Swine Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-064-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1056; Swine; Nursery pigs; Wheat middlings